3-Chloroplumbagin Induces Cell Death in Breast Cancer Cells Through MAPK-Mediated Mcl-1 Inhibition - Kawiak, Anna; Domachowska, Anna; Krolicka, Aleksandra; Smolarska, Monika; Lojkowska, Ewa (Frontiers in Pharmacology, 2019)
Resistance acquired towards anti-cancer agents is a major drawback in breast cancer therapy. A key factor contributing to drug resistance is apoptosis suppression associated with the upregulation of anti-apoptotic Bcl-2 family proteins. Specifically, the anti-apoptotic Mcl-1 protein has been shown to play a significant role in drug resistance making it an important therapeutic target. The present study aimed at determining the antiproliferative activity of 3-chloroplumbagin (ChPL), a naphthoquinone derived from a Dionaea sp., toward breast cancer cells and examining the involvement of Mcl-1 inhibition in ChPL-induced cell death. The results showed that ChPL inhibited breast cancer cell proliferation and induced apoptosis through the intrinsic pathway through down-regulation of anti-apoptotic Bcl-2 family proteins. The induction of apoptosis by ChPL was found to be mediated through MAP kinase signaling inhibition. The phosphorylation of MEK and ERK proteins was inhibited by ChPL in breast cancer cells and ChPL-induced apoptosis increased in cells with reduced ERK expression. Furthermore, ERK silencing decreased the expression of Mcl-1 in ChPL-treated cells. The results of this research indicate that ChPL induces apoptosis in breast cancer cells through MAPK-mediated Mcl-1 inhibition, suggesting further research into its potential in breast cancer treatment.